Revisando a Loxanthocereus riomajensis, lectotipificación, biogeografía y estado de conservación de una especie endémica de Arequipa, Perú - Pauca Tanco, G. Anthony (2024)
This study aims to clarify the taxonomy of Loxanthocereus riomajensis, as well as to understand its actual and potential geographic distribution, and to present its conservation status. Specialized literature was reviewed, and field visits were conducted. The collected data, including herbarium samples, presence records, and additional information, were used to describe the species in detail, create a geographical distribution map, generate potential distribution models using the MaxEnt algorithm, and assess its conservation status using IUCN considerations. The results demonstrate that morphologically, L. riomajensis is an independent species endemic to the departament of Arequipa, found in the provinces of Condesuyos and Caylloma, spanning an altitudinal range from 1600 to 2100 m asl. The potential distribution covers an area of 1135.3 km2, in the provinces of Condesuyos, Castilla, La Unión, Caravelí, Caylloma, and Arequipa. Regarding its conservation status, it is classified as endangered (EN). Finally, a lectotype is designated.